The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Experimental manipulation of population density in a wild bird alters social structure but not patch discovery rate - Kristina B. Beck; Charlotte E. Regan; Keith McMahon; Sam Crofts; Ella F. Cole; Josh A. Firth; Ben C. Sheldon (Animal Behaviour, 2024)

Temperature synchronizes temporal variation in laying dates across European hole‐nesting passerines - Stefan J. G. Vriend; Vidar Grøtan; Marlène Gamelon; Frank Adriaensen; Markus P. Ahola; Elena Álvarez; Liam D. Bailey; Emilio Barba; Jean‐Charles Bouvier; Malcolm D. Burgess; Andrey Bushuev; Carlos Camacho; et al. (Ecology, 2023)
Identifying the environmental drivers of variation in fitness‐related traits is a central objective in ecology and evolutionary biology. Temporal fluctuations of these environmental drivers are often synchronized at large spatial scales. Yet, whether synchronous environmental conditions can generate spatial synchrony in fitness‐related trait values (i.e., correlated temporal trait fluctuations across populations) is poorly understood. Using data from long‐term monitored populations of blue tits ( Cyanistes caeruleus , n = 31), great tits ( Parus major , n = 35), and pied flycatchers ( Ficedula hypoleuca , n = 20) across Europe, we assessed the influence of two local climatic variables (mean temperature and mean precipitation in February–May) on spatial synchrony in three fitness‐related traits: laying date, clutch size, and fledgling number. We found a high degree of spatial synchrony in laying date but a lower degree in clutch size and fledgling number for each species. Temperature strongly influenced spatial synchrony in laying date for resident blue tits and great tits but not for migratory pied flycatchers. This is a relevant finding in the context of environmental impacts on populations because spatial synchrony in fitness‐related trait values among populations may influence fluctuations in vital rates or population abundances. If environmentally induced spatial synchrony in fitness‐related traits increases the spatial synchrony in vital rates or population abundances, this will ultimately increase the risk of extinction for populations and species. Assessing how environmental conditions influence spatiotemporal variation in trait values improves our mechanistic understanding of environmental impacts on populations.

Description of two new bird species from the Meratus Mountains of southeast Borneo, Indonesia - Mohammad Irham; Tri Haryoko; Subir B. Shakya; Simon L. Mitchell; Ryan C. Burner; Carlos Bocos; James A. Eaton; Frank E. Rheindt; Suparno Suparno; Frederick H. Sheldon; Dewi M. Prawiradilaga (Journal of Ornithology, 2022)

Biotic interactions help explain variation in elevational range limits of birds among Bornean mountains - Ryan C. Burner; Andy J. Boyce; David Bernasconi; Alison R. Styring; Subir B. Shakya; Chandradewana Boer; Mustafa Abdul Rahman; Thomas E. Martin; Frederick H. Sheldon (Journal of Biogeography, 2020)
Aim Physiological tolerances and biotic interactions along habitat gradients are thought to influence species occurrence. Distributional differences caused by such forces are particularly noticeable on tropical mountains, where high species turnover along elevational gradients occurs over relatively short distances and elevational distributions of particular species can shift among mountains. Such shifts are interpreted as evidence of the importance of spatial variation in interspecific competition and habitat or climatic gradients. To assess the relative importance of competition and compression of habitat and climatic zones in setting range limits, we examined differences in elevational ranges of forest bird species among four Bornean mountains with distinct features. Location Bornean mountains Kinabalu, Mulu, Pueh and Topap Oso. Taxon Rain forest bird communities along elevational gradients. Methods We surveyed the elevational ranges of rain forest birds on four mountains in Borneo to test which environmental variables—habitat zone compression or presence of likely competitors—best predicted differences in elevational ranges of species among mountains. For this purpose, we used two complementary tests: a comparison of elevational range limits between pairs of mountains, and linear mixed models with naïve occupancy as the response variable. Results We found that lowland species occur higher in elevation on two small mountains compared to Mt. Mulu. This result is inconsistent with the expectation that distributions of habitats are elevationally compressed on small mountains, but is consistent with the hypothesis that a reduction in competition (likely diffuse) on short mountains, which largely lack montane specialist species, allows lowland species to occur higher in elevation. The relative influence of competition changes with elevation, and the correlation between lower range limits of montane species and the distribution of their competitors was weaker than in lowland species. Main conclusions These findings provide support for the importance of biotic interactions in setting elevational range limits of tropical bird species, although abiotic gradients explain the majority of distribution patterns. Thus, models predicting range shifts under climate change scenarios must include not only climatic variables, as is currently most common, but also information on potentially resulting changes in species interactions, especially for lowland species.

Fast analysis of caffeinated beverages using laser diode thermal desorption mass spectrometry (LDTD-MS/MS) - Wendy C. Andersen; Michael VanSickle; Joseph Storey; Virginia Sheldon; Jack Lohne; Sherri B. Turnipseed; Terri Thomas; Mark Madson (Food Additives & Contaminants: Part A, 2019)

Individual personalities predict social behaviour in wild networks of great tits ( Parus major) - L. M. Aplin; D. R. Farine; J. Morand‐Ferron; E. F. Cole; A. Cockburn; B. C. Sheldon (Ecology Letters, 2013)
Social environments have an important effect on a range of ecological processes, and form a crucial component of selection. However, little is known of the link between personality, social behaviour and population structure. We combine a well‐understood personality trait with large‐scale social networks in wild songbirds, and show that personality underpins multiple aspects of social organisation. First, we demonstrate a relationship between network centrality and personality with ‘proactive’ (fast‐exploring) individuals associating weakly with greater numbers of conspecifics and moving between flocks. Second, temporal stability of associations relates to personality: ‘reactive’ (slow‐exploring) birds form synergistically stable relationships. Finally, we show that personality influences social structure, with males non‐randomly distributed across groups. These results provide strong evidence that songbirds follow alternative social strategies related to personality. This has implications not only for the causes of social network structure but also for the strength and direction of selection on personality in natural populations.

Corrigendum - J. R. CHAPMAN; S. NAKAGAWA; D. W. COLTMAN; J. SLATE; B. C. SHELDON (Molecular Ecology, 2011)

Are Great Tits (Parus major) Inhabiting the Vicinity of a Pulp Mill Healthy? Impacts on Physiology and Breeding Performance - Ana Cláudia Norte; B. C. Sheldon; J. P. Sousa; P. C. Tavares; M. E. Pereira; A. C. Duarte; J. A. Ramos (Archives of Environmental Contamination and Toxicology, 2010)

Biogeographical patterns of blood parasite lineage diversity in avian hosts from southern Melanesian islands - Farah Ishtiaq; Sonya M. Clegg; Albert B. Phillimore; Richard A. Black; Ian P. F. Owens; Ben C. Sheldon (Journal of Biogeography, 2010)
Aim (1) To describe the species–area relationships among communities of Plasmodium and Haemoproteus parasites in different island populations of the same host genus (Aves: Zosterops ). (2) To compare distance–decay relationships (turnover) between parasite communities and those with potential avian and dipteran hosts, which differ with respect to their movement and potential to disperse parasite species over large distances. Location Two archipelagos in the south‐west Pacific, Vanuatu and New Caledonia ( c . 250 km west of Vanuatu) and its Loyalty Islands, with samples collected from a total of 16 islands of varying sizes (328–16,648 km 2 ). Methods We characterized parasite diversity and distribution via polymerase chain reaction (PCR) from avian ( Zosterops ) blood samples. Bayesian methods were used to reconstruct the parasite phylogeny. In accordance with recent molecular evidence, we treat distinct mitochondrial DNA lineages as equivalent to species in this study. Path analysis and parasite lineage accumulation curves were used to assess the confounding effect of inadequate sampling on the estimation of parasite richness. Species–area and species–distance relationships were assessed using linear regression: distance–decay relationships were assessed using Mantel tests. Results Birds and mosquito species and Plasmodium lineages exhibited significant species–area relationships. However, Plasmodium lineages showed the weakest ‘species–area’ relationship; no relationship was found for Haemoproteus lineages. Avian species richness influenced parasite lineage richness more than mosquito species richness did. Within individual avian host species, the species–area relationship of parasites showed differing patterns. Path analysis indicated that sampling effort was unlikely to have a confounding effect on parasite richness. Distance from mainland (isolation effect) showed no effect on parasite richness. Community similarity decayed significantly with distance for avifauna, mosquito fauna and Plasmodium lineages but not for Haemoproteus lineages. Main conclusions Plasmodium lineages and mosquito species fit the power‐law model with steeper slopes than found for the avian hosts. The lack of species–distance relationship in parasites suggests that other factors, such as the competence of specific vectors and habitat features, may be more important than distance. The decay in similarity with distance suggests that the sampled Plasmodium lineages and their potential hosts were not randomly distributed, but rather exhibited spatially predictable patterns. We discuss these results in the context of the effects that parasite generality may have on distribution patterns.

Variation of adult Great Tit Parus major body condition and blood parameters in relation to sex, age, year and season - A. C. Norte; J. A. Ramos; J. P. Sousa; B. C. Sheldon (Journal of Ornithology, 2009)

A quantitative review of heterozygosity–fitness correlations in animal populations - J. R. CHAPMAN; S. NAKAGAWA; D. W. COLTMAN; J. SLATE; B. C. SHELDON (Molecular Ecology, 2009)
The ease of obtaining genotypic data from wild populations has renewed interest in the relationship between individual genetic diversity and fitness‐related traits (heterozygosity–fitness correlations, or HFC). Here we present a comprehensive meta‐analysis of HFC studies using powerful multivariate techniques which account for nonindependence of data. We compare these findings with those from univariate techniques, and test the influence of a range of factors hypothesized to influence the strength of HFCs. We found small but significantly positive effect sizes for life‐history, morphological, and physiological traits; while theory predicts higher mean effect sizes for life‐history traits, effect size did not differ consistently with trait type. Newly proposed measures of variation were no more powerful at detecting relationships than multilocus heterozygosity, and populations predicted to have elevated inbreeding variance did not exhibit higher mean effect sizes. Finally, we found evidence for publication bias, with studies reporting weak, nonsignificant effects being under‐represented in the literature. In general, our review shows that HFC studies do not generally reveal patterns predicted by population genetic theory, and are of small effect (less than 1% of the variance in phenotypic characters explained). Future studies should use more genetic marker data and utilize sampling designs that shed more light on the biological mechanisms that may modulate the strength of association, for example by contrasting the strength of HFCs in mainland and island populations of the same species, investigating the role of environmental stress, or by considering how selection has shaped the traits under investigation.

Avian haematozoan parasites and their associations with mosquitoes across Southwest Pacific Islands - F. ISHTIAQ; L. GUILLAUMOT; S. M. CLEGG; A. B. PHILLIMORE; R. A. BLACK; I. P. F. OWENS; N. I. MUNDY; B. C. SHELDON (Molecular Ecology, 2008)
The degree to which haematozoan parasites can exploit a range of vectors and hosts has both ecological and evolutionary implications for their transmission and biogeography. Here we explore the extent to which closely related mosquito species share the same or closely related haematozoan parasites, and examine the overlap in parasite lineages with those isolated from avian hosts, Zosterops species, sampled across the same study sites. Mosquito samples were collected and analysed (14 species, n = 804) from four islands in Vanuatu and the main island of New Caledonia. Using polymerase chain reaction, 15.5% (14/90) of pooled mosquito (thoracic) samples showed positive amplifications. Subsequent phylogenetic analysis of the cytochrome b gene identified four genetically distinct Plasmodium and two Haemoproteus lineages from these samples, five of which were identical to parasite lineages ( n = 21) retrieved from the avian hosts. We found that three Plasmodium lineages differing by a maximum of 0.9% sequence divergence were recovered from different species and genera of mosquitoes and two Haemoproteus lineages differing by 4.6% sequence divergence were carried by 10 distantly related (11–21% divergent) mosquito species. These data suggest a lack of both cospeciation and invertebrate host conservatism. Without experimental demonstration of the transmission cycle, it is not possible to establish whether these mosquitoes are the biological vectors of isolated parasite lineages, reflecting a limitation of a purely polymerase chain reaction‐based approach. Nonetheless, our results raise the possibility of a new transmission pathway and highlight extensive invertebrate host shifts in an insular mosquito–parasite system.

Senescence rates are determined by ranking on the fast–slow life‐history continuum - Owen R. Jones; Jean‐Michel Gaillard; Shripad Tuljapurkar; Jussi S. Alho; Kenneth B. Armitage; Peter H. Becker; Pierre Bize; Jon Brommer; Anne Charmantier; Marie Charpentier; Tim Clutton‐Brock; F. Stephen Dobson; et al. (Ecology Letters, 2008)
Comparative analyses of survival senescence by using life tables have identified generalizations including the observation that mammals senesce faster than similar‐sized birds. These generalizations have been challenged because of limitations of life‐table approaches and the growing appreciation that senescence is more than an increasing probability of death. Without using life tables, we examine senescence rates in annual individual fitness using 20 individual‐based data sets of terrestrial vertebrates with contrasting life histories and body size. We find that senescence is widespread in the wild and equally likely to occur in survival and reproduction. Additionally, mammals senesce faster than birds because they have a faster life history for a given body size. By allowing us to disentangle the effects of two major fitness components our methods allow an assessment of the robustness of the prevalent life‐table approach. Focusing on one aspect of life history – survival or recruitment – can provide reliable information on overall senescence.

Stability of genetic variance and covariance for reproductive characters in the face of climate change in a wild bird population - DANY GARANT; JARROD D. HADFIELD; LOESKE E. B. KRUUK; BEN C. SHELDON (Molecular Ecology, 2008)
Global warming has had numerous effects on populations of animals and plants, with many species in temperate regions experiencing environmental change at unprecedented rates. Populations with low potential for adaptive evolutionary change and plasticity will have little chance of persistence in the face of environmental change. Assessment of the potential for adaptive evolution requires the estimation of quantitative genetic parameters, but it is as yet unclear what impact, if any, global warming will have on the expression of genetic variances and covariances. Here we assess the impact of a changing climate on the genetic architecture underlying three reproductive traits in a wild bird population. We use a large, long‐term, data set collected on great tits ( Parus major ) in Wytham Woods, Oxford, and an ‘animal model’ approach to quantify the heritability of, and genetic correlations among, laying date, clutch size and egg mass during two periods with contrasting temperature conditions over a 40‐year period (1965–1988 [cooler] vs. 1989–2004 [warmer]). We found significant additive genetic variance and heritability for all traits under both temperature regimes. We also found significant negative genetic covariances and correlations between clutch size and egg weight during both periods, and among laying date and clutch size in the colder years only. The overall G matrix comparison among periods, however, showed only a minor difference among periods, thus suggesting that genotype by environment interactions are negligible in this context. Our results therefore suggest that despite substantial changes in temperature and in mean laying date phenotype over the last decades, and despite the large sample sizes available, we are unable to detect any significant change in the genetic architecture of the reproductive traits studied.

Antagonistic natural selection revealed by molecular sex identification of nestling collared flycatchers - J. Merilä; B. C. Sheldon; H. Ellegren (Molecular Ecology, 1997)
Natural selection may act in different directions during different life‐history stages, or in different directions on different classes of individuals. Antagonistic selection of this kind may be an important mechanism by which additive genetic variation for quantitative traits is maintained, and can prevent populations or species reaching local adaptive peaks. This paper reports the results of a study of viability selection on morphological traits of nestling collared flycatchers Ficedula albicollis . Analyses performed without knowledge of the sex of nestlings suggested that no selection was occurring on these traits. However, using molecular sex identification with the avian CHD gene, it is shown that selection acts in different directions on male and female body size from fledging to breeding, apparently favouring relatively small males and large females. The results suggest that differential selection on male and female nestlings may contribute to purely phenotypic sexual size dimorphism in this species. These findings highlight the potential of newly developed molecular sexing techniques to reveal the consequences of an individual's gender for many aspects of its life history in taxa where gender cannot be determined on the basis of external appearance.

Copulation behavior and paternity in the chaffinch - B. C. Sheldon; T. Burke (Behavioral Ecology and Sociobiology, 1994)